APC-Pengaruh Pemberian Blastocystis sp. Terhadap Jumlah Leukosit Pada Tikus - Febriyanti, Rizka; Nofita, Eka; Afriani, Nita; Adrial, Adrial; Asri, Aswiyanti; Almurdi, Almurdi (Jurnal Penelitian Kesehatan SUARA FORIKES, 2025)
Blastocystis sp. are the most common intestinal protists in human and animal faeces. Blastocystis sp infection associated with inhibition of celluler immunity due to an increase in cytokines resulting in an increase in the number of leukocytes. This study was conducted to determine the correlation between Blastocystis sp infection and leukocyte count. This experimental study with a post test only control group design, used male Wistar white rats (Rattus norvegicus). Blastocystis sp infection in rats assessed by performing microscopic examination of rat faeces and culture. Leukocytes count examination was carried out using a counting chamber. Data analysis was carried out using the One Way Anova Test. The final results obtained were the mean number of leukocytes in treatment group 1 (P1), treatment 2 (P2) negative control (K-) respectively, 6171.43 cells/mm3, 6866.67 cells/mm3 , and 7742.86 cells/mm3 mm3. The p value of One Way Anova p = 0.7 (p > 0.05). The conclusion is the administration of Blastocystis sp. did not significantly influence the number of rat leukocytes.Keywords: blastocystis sp; leukocyte count; rattus norvegicus